The Effect of Administration of Oral Sucrose to Pain Intensity on Infant with DPT-HB (DPT combo) Immunization at Puskesmas II Denpasar Timur. - Taryanthi, Ni Made (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
Immunization is the most frequent repeated processes that produce pain at pediatric nursing. Pain due to immunization has short and long-term effects on infant. The paradigm of pediatric nursing had changed through atraumatic care approaches which minimalize pain. One of the non pharmacological interventions that cheap, non invasive and quick onset of work which can be administered is oral sucrose, an agent that could produces analgesic effect through endogen opioid receptor activation. This study objective is to assess administration effect of oral sucrose to pain intensity on infant with DPT-HB (DPT Combo) immunization. It is a pre-experimental study with static group comparison design. Sample consists of 40 infants, randomly assigned by purposive sampling. The sample is divided into 2 groups, intervention and control ones. Data gathering uses assessment paper to know the respondent characteristics while DAN score with structure observation was used to assess the pain intensity. The result of 20 sample of intervention group is 35% suffers mild, 60% moderate and 5% severe pain while 20 sample of control, 5% suffers moderate and the rest 95% with severe pain. Based on Mann Whitney U-test, this difference is statistically significant with p=0.000 which means there is effect of oral sucrose administration to pain intensity on infant with DPT-HB (DPT Combo) immunization. This study recommends the health professional to use oral sucrose on immunization process to reduce pain intensity.
Keywords: immunization, pain, oral sucrose